الفكر الديني وتأثيرهُ على مجتمع بلاد الرافدين - هاشم, زينة قاسم (Al-Adab Journal, 2019)
Religious Thought and its Influence on the Society of Mesopotamia Introduction The inhabitants of Mesopotamia have taken the naturalization of nature and the greater powers it possesses than the human forces in its Own way, And thought that these powers a human spirit with dangerous energies, as the Semites thought that the trees and caves and Springs and stones consumed by the livws. Conclusion:The Multiplicity of the gods of Sumerian, Babylonian and Assyrian, due to the multiplicity of natural phenomena such as the sky and the stars and planets, and the earth and the mountains and rivers and Valleys, plant and animal.The people of Mesopotamia looked at nature as being associated with it, in a way that believed that every aspect of nature has a god.